Long-term cost-effectiveness analysis shows that IDegLira is associated with improved outcomes and lower costs compared with insulin glargine U100 plus insulin aspart in the US. (2nd November 2018) - Dempsey, Michael; Mocarski, Michelle; Langer, Jakob; Hunt, Barnaby
Abstract: Aims: The clinical and economic impact of diabetes is growing in the US. Choosing therapies that are both effective and cost-effective is becoming increasingly important. The aim of the present analysis was to assess the long-term cost-effectiveness of IDegLira for treatment of patients with type 2 diabetes mellitus not meeting glycemic targets on basal insulin, vs insulin glargine U100 plus insulin aspart, in the US setting. Materials and methods: Long-term projections of cost-effectiveness outcomes were made using the IQVIA CORE Diabetes Model. Clinical inputs were based on the DUAL VII trial, with costs (accounted from a healthcare payer perspective) and utilities based on published sources. Future costs and clinical benefits were discounted at 3% annually. Results: IDegLira was associated with increased discounted life expectancy by 0.02 years and increased discounted quality-adjusted life expectancy by 0.22 quality-adjusted life years compared with insulin glargine U100 plus insulin aspart. Evaluation of direct medical costs suggested that the mean cost per patient with IDegLira was 3, 571 lower than with insulin glargine U100 plus insulin aspart. The cost saving was driven predominantly by the lower acquisition cost of IDegLira compared with insulin glargine U100 plus insulin aspart, with further cost savings identified as a result of avoided treatment of diabetes-related complications. IDegLira was associated with improved clinical outcomes at a reduced cost compared with insulin glargine U100 plus insulin aspart. Conclusions: Based on clinical trial data, the present analysis suggests that IDegLira is associated with improved clinical outcomes and cost savings compared with treatment with insulin glargine U100 plus insulin aspart for patients with type 2 diabetes not achieving glycemic control on basal insulin in the US. Therefore, IDegLira is likely to be considered dominant (cost saving and more effective) and, consequently, highly cost-effective in the US setting.